Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.proche.2015.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Discharge in Active Metallic Grains for Water Purification Processes

Abstract: Chemical reactions in electric metal pulse dispersion in the aqueous solutions of inorganic substance (НSiO[3]{–}, Ni{2+}, Н[2]AsO[4]{–}, Mn{2+}, Cr[2]O[7]{2–}) were determined through IR spectroscopy, X-ray phase, chemical, kinetic, and thermodynamic analyses. Under such conditions, both reduction and oxidation reactions occur, as well as, locally initiated by heating, hydrolysis and exchange reactions without changing the oxidation rate of the dissolved substance itself. Reduction and oxidation of dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Apart from food processing, the technology has been successfully utilized as a novel extraction technique in the area of bioprocessing (Table 1). It has enhanced the yield of potential bioactive compounds and other cellular components from various plants, fruits, vegetables, algae, oil seeds and other food matrices (Griffiths and Walkling-Ribeiro 2014, Toepfl et al 2014, Shakhova et al 2015, Amiali and Ngadi 2012. Furthermore, it has also demonstrated a positive influence in the texture of solid plant foods and has found a significant application in reducing the sludge of wastewater (Nasir et al 2016).…”
Section: Pulsed Electric Field Processingmentioning
confidence: 99%
“…Apart from food processing, the technology has been successfully utilized as a novel extraction technique in the area of bioprocessing (Table 1). It has enhanced the yield of potential bioactive compounds and other cellular components from various plants, fruits, vegetables, algae, oil seeds and other food matrices (Griffiths and Walkling-Ribeiro 2014, Toepfl et al 2014, Shakhova et al 2015, Amiali and Ngadi 2012. Furthermore, it has also demonstrated a positive influence in the texture of solid plant foods and has found a significant application in reducing the sludge of wastewater (Nasir et al 2016).…”
Section: Pulsed Electric Field Processingmentioning
confidence: 99%
“…In food processing it is used successfully for several types of fruit. The analyses have shown that they cause a minimal negative effect on the physical and sensory properties but increase the shelf life and the functional and textural properties of the juices [95,100].…”
Section: Pulsed Electric Field Processingmentioning
confidence: 99%